(1/6)(2x+64)=3x

Simple and best practice solution for (1/6)(2x+64)=3x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (1/6)(2x+64)=3x equation:


(1/6)(2x+64)=3x

We simplify the equation to the form, which is simple to understand
(1/6)*(2x+64)=3x

Simplifying:
( + 0.166666666667)*(2x+64)=3x

Reorder the terms in parentheses
multiplication of parentheses
( + 0.333333333333x+10.6666666667)=3x



Remove unnecessary parentheses
+ 0.333333333333x+10.6666666667=3x

We move all terms containing x to the left and all other terms to the right.
+ 0.333333333333x-3x=-10.6666666667

We simplify left and right side of the equation.
-2.66666666667x=-10.6666666667

We divide both sides of the equation by -2.66666666667 to get x.
x=4.00000000001

See similar equations:

| 45x^3+105x^2+50x=0 | | 3x-27=54+12x | | 30+11x+x^2=0 | | 110x^2+21x-110=0 | | 5a+5(1)=9 | | 180n-360=(n-2)180 | | u^2-16u+10=0 | | 4y+7=2x-21 | | H=WQx | | a^2-9ab+14b^2=0 | | 8.45+3.3+6= | | 9c^2-10c+1=0 | | 8x+5y-z=0 | | x+3x+6x-6=180 | | 4x=3+8 | | 4(x-4)=4x+32 | | 35x^2+93x+54=0 | | -4x+7y=27 | | 3(x+3)+3=-15(x+2) | | -7x-14-14=5x | | 35x^2+83x+54=0 | | log(3)(x+16)-log(3)(x-10)=3 | | 4x+5y=-19 | | 2a^2-9a=0 | | (.5)(2x+32)=5x | | x+4y=-2 | | 5x^2=16x+16 | | 98x^3+98x^2+20x=0 | | 98x^3+98x+20x=0 | | (x+2)(x)(3)=0 | | 4(x+21)=-3(x-21) | | 49x^2+49x+10=0 |

Equations solver categories